Adjudication and discretion - Waluchow, W (1980)
This thesis is mainly a critical examination of Professor R.M. Dworkin's recent attack upon the theory of judicial discretion. Dworkin is concerned to attack the theory in all of its forms, but he uses Professor H.L.A. Hart's version as his principal target. The examination therefore concentrates on Dworkin's attack upon Hart. Following a short Introduction, Hart's theory of adjudication andits constituent theory of judicial discretion are investigated in chapter two. In the remaining four chapters Dworkin's response to hart's views is considered. Chapter three isolates four main themes around which Dworkin centres his attack: that hart's theory (a) fails to distinguish weak and strong discretion, (b) is morally and politically unattractive, (c) is not true to the facts of the Anglo-American adjudicative process, and (d) is the consequence of an inadequate conception of law -- the model of rules. An attempt is made in chapter three to refute (b) and (c), and to determine the exact meaning of 'strong discretion'. An important distinction between having discretion and exercising discretion or discretionary judgment is also noted. Chapter four contains an analysis of Dworkin's theories about rules, principles and policies, and chapter five attempts to refute Dworkin's claim that Hart's theories of law and adjudication must restrict binding law to valid rules. In chapter six Dworkin's alternative theories are considered. It is argued that judges would inevitably have (strong) discretion and would inevitably be led to exercise (strong) discretionary judgment, even if the law included all that Dworkin says it does, and even if judges decided cases in the way in which Dworkin says they do. From this it is concluded that Dworkin has failed in his bid to refute the theory of judicial discretion.